Risk Factors of Musculoskeletal Disorders among Workers of Water Refilling Depot - Hulu, Victor Trismanjaya; Manalu, Putranto; Siregar, Santy Deasy; Singa, Aditya Bastanta Guru; Amrulah, Addin (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2023)
Complaints of musculoskeletal disorders (MSDs) are common in workers with a reasonably heavy workload, such as workers at refill drinking water depots. MSDs can be caused by repetitive activities such as daily bending, lifting and lowering liters of drinking water refills. This study aimed to identify the risk factors of MSDs among workers at refilled drinking water filling depots and analyze the dominant factors that influence MSDs. This study was quantitative research with an analytical survey using a cross-sectional design conducted in Simpang Selayang Village, Medan City, Indonesia. A total of 40 refilled drinking water depot workers were involved in this study with a comprehensive sampling approach. Data was collected directly by distributing questionnaires to workers at refill drinking water filling depots. Data were tested statistically using the Chi-Square test and logistic regression. The analysis showed that work posture, workload, tenure and length of work are associated with MSDs complaints. The results of the logistic regression test showed that the dominant variable influencing MSDs complaints is work posture. Refillable drinking water depot workers with non-ergonomic working postures were likely to experience MSDs complaints 11 times as often as those with ergonomic work postures. The findings highlight the need for local health agencies to educate or empower workers at water refilling stations regarding MSDs complaints. Musculoskeletal disorders associated with work involving heavy loads could be prevented if workers know ergonomic work postures well. In addition, adequate rest is recommended to avoid musculoskeletal injuries.